Outcome of anticoagulation in isolated distal deep vein thrombosis compared to proximal deep venous thrombosis. (21st July 2021) - Vlazny, Danielle T.; Pasha, Ahmed K.; Kuczmik, Wiktoria; Wysokinski, Waldemar E.; Bartlett, Matthew; Houghton, Damon; Casanegra, Ana I.; Daniels, Paul; Froehling, David A.; White, Launia J.; Hodge, David O.; McBane, Robert D.
Abstract: Background: Isolated, distal deep vein thrombosis (IDDVT) is thought to have low rates of propagation, embolization, and recurrence compared with proximal DVT (PDVT), but the data are limited. Objectives: The objective of this study was to assess outcomes among patients with IDDVT compared with PDVT. Patients/Methods: Consecutive patients with ultrasound‐confirmed acute DVT (March 1, 2013–August 1, 2020) were identified by reviewing the Mayo Clinic Gonda Vascular Center and VTE Registry databases. Patients were divided into two groups depending on the DVT location (isolated, distal vs. proximal DVT). Outcomes including venous thromboembolism (VTE) recurrence, major bleeding, and death were compared by thrombus location and anticoagulant therapy, warfarin vs. direct oral anticoagulant (DOAC). Results: Isolated, distal deep vein thrombosis ( n = 746) was more often associated with recent surgery, major trauma, or confinement ( p < .001), whereas patients with PDVT ( n = 1176) were more frequently unprovoked, had a prior history of VTE, or active cancer ( p < .001). There was no overall difference in VTE recurrence or major bleeding between groups during follow‐up. Patients with IDDVT had a higher death rate at 3 months ( p = .001) and when propensity scored for cancer ( p = .003). Independent predictors of mortality included warfarin (vs. DOAC) therapy, increasing age, and active cancer. DOAC therapy resulted in lower VTE recurrence, major bleeding, and death rates in both groups. Conclusion: Outcomes of IDDVT including VTE recurrence and bleeding rates were similar to PDVT despite higher early mortality rates. Outcomes for both groups were positively influenced by the use of DOACs.